The structure of the Malay emotional concepts of marah (anger), sabar (patience), and hormat (respect) among IIUM employees - Sari, Santika (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
This study sought to explore the structure of three emotion concepts in the Malay culture, namely, marah 'anger', sabar 'patience', and hormat 'respect' using the prototype approach. Two studies (Study 1 and Study 2) were conducted. Study 1 aimed to examine the words that best portray the three concepts using prototypical ratings. In Study 2, 100 nonacademic employees at International Islamic University Malaysia were involved in card sorting procedure. A total of 82 words were sorted and categorized using hierarchical cluster analysis and yielded a comprehensive tree-like hierarchy of marah, sabar, and hormat. The three levels of inclusiveness in the hierarchy are; 1. Superordinate level (positive and negative emotion category); 2. Basic level (sabar 'patience', hormat 'respect', tenang 'calmness', and marah 'anger'); and 3. Subordinate level. The superordinate level confirms previous findings indicating its universality, whereas the subordinate level depicts the indigenous nature of the three emotion concepts. The basic level may not be concluded as universal or culturally unique because this level needs further evidences from different studies with the same lexicons.